Hubungan Usia Ibu Postpartum dengan Kejadian Depresi Postpartum di Posyandu Desa Wadunggetas: Hubungan usia ibu post partum dengan kejadian depresi post partum di posyandu desa wadunggetas - Sinta Septiana Devi; Dewi Kartika Sari (Universitas Duta Bangsa Surakarta, 2023)
ABSTRACT Introduction: Postpartum depression is a mood disorder that occurs after childbirth. This disorder reflects the psychological dysregulation that is a hallmark of major depressive symptoms. Based on the WHO report it is estimated that Postpartum women who experience mild postpartum depression range from 10 per 1000 live births and moderate or severe postpartum depression range from 30 to 200 per 1000 live births.Objectives: This study aims to analyze the relationship between postpartum maternal age and the incidence of postpartum depression at the posyandu in Wadunggetas villageMethods: The research subjects were 22 postpartum mothers at posyandu in Wadunggetas village. This study used the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. Data were analyzed with statistical product and service solutions (SPSS).Results: the results showed that the Rank-Spearman test proved that there was a relationship between postpartum maternal age and the inicidence of postpartum depression at the posyandu wadunggetas village with p value=0,006 the incidence of postpartum depression at posyandu using the EPDS questionnaire was 9 postpartum mothers (40.9%) who just had a baby or experienced the baby blues, 6 postpartum mothers (27.3%) showed symptoms of depression. The risk factors obtained in this study were postpartum maternal age 35 years.Conclusions: the incidence of postpartum depression at the posyandu in Wadunggetas village based on the EPDS score is 40.9%.Keyword: Age, Postpartum, Depression Pendahuluan: Postpartum depresi merupakan gangguan mood yang terjadi setelah melahirkan. gangguan ini merefleksikan disregulasi psikologikal yang merupakan tanda dari gejala-gejala depresi mayor. Berdasarkan laporan WHO diperkirakan wanita melahikan yang mengalami Postpartum Depresi ringan berkisar 10 per 1000 kelahiran hidup dan Postpartum Depresi sedang atau berat berkisar 30 sampai 200 per 1000 kelahiran hidup.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara usia ibu postpartum dengan kejadian depresi postpartum di posyandu desa Wadunggetas.Metode: Subjek penelitian adalah 22 ibu postpartum di posyandu desa Wadunggetas. Penelitian ini menggunakan kuesioner Edinburgh Postnatal Depression Scale (EPDS). Data dianalisa dengan statistical product and service solutions (SPSS).Hasil: hasil penelitian menunjukkan bahwa uji Rank-Spearman membuktikan adanya hubungan antara usia ibu postpartum dengan kejadian depresi postpartum di posyandu desa wadunggetas dengan p value =0,006. kejadian depresi postpartum di posyandu menggunakan kuesioner EPDS sebanyak 9 ibu postpartum (40,9%) baru pengalaman memiliki bayi atau mengalami baby blues,6 ibu postpartum (27,3%) menunjukkan gejala depresi.faktor resiko yang didapat dalam penelitian ini adalah usia ibu postpartum 35 tahun.Kesimpulan: kejadian depresi postpartum di posyandu desa Wadunggetas berdasarkan skor EPDS adalah 40,9%.Kata Kunci: Usia, Depresi, Postpartum Jurnal Keperawatan Duta Medika diterbitkan oleh Universitas Duta Bangsa Surakarta.Website: ojs.udb.ac.id